Methodological aspects of the lesson «The primary (autonomous) lesions of the oral mucosa». - Dmitrieva, E. O. (Морфологія / Morphologia / Morfologìâ, 2014)
The article presents the main methodological aspects of practical training in one of the most extensive and difficult sections of therapeutic dentistry - oral pathology. The article is focused on a variety of diseases of oral mucous membrane in accordance with the etiology, pathogenesis, clinical manifestations, on the classification issues, general principles and particular methods of diagnosis, which dictates the requirements for a student to be fully aware of semiotics of oral mucous membrane diseases, have a good command of clinical and diagnostic research methods, patient treatment and disease prevention methods.